The Painted Forest - Eastman, Krista (Book collections on Project MUSE., 2019)
"Collection of creative essays about identity and place set in various locations in Wisconsin (including Sauk County, the Dells, the Driftless, Ernest Hupeden's The Painted Forest in Valton) and McMurdo Station in Antarctica"--